2018
DOI: 10.1016/j.pmedr.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

The association between long work hours and leisure-time physical activity and obesity

Abstract: Obesity affects approximately one-third of all U.S. adults, presenting a large economic and public health burden. Long work hours may be contributing to the rising obesity problem by reducing time for physical activity, particularly for individuals working in sedentary occupations. This study sought to investigate the association between long work hours, leisure-time physical activity (LTPA), and obesity across levels of occupational activity in order to identify potentially vulnerable groups. Cross sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 40 publications
(60 reference statements)
7
42
0
Order By: Relevance
“…The author prophesied that long years of experience might play a significant role in better managing time and energy during working hour; thus, more time could be dedicated to physical activity and exercise. While this study did not find significant differences between working experience groups workers with lower experience years (less than 5 years) tend to be more affected by physical activity barriers than the group with more extended experience (more than 10 years).The current results are in agreement with evidence that suggested that the effect of long work hours on physical activity levels and meeting the recommendations among employees working status (including occupations type, and years of experience) consider as an effect modifier in the relationship, affecting differently across occupations (Cook & Gazmararian, 2018). Research studies have related the impact of working hours on employees physical activity levels to the professional level occupation, whereas, those with higher occupational level were more likely to be more active and meet the leisure-time physical activity recommendations (Kirk & Rhodes, 2011).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The author prophesied that long years of experience might play a significant role in better managing time and energy during working hour; thus, more time could be dedicated to physical activity and exercise. While this study did not find significant differences between working experience groups workers with lower experience years (less than 5 years) tend to be more affected by physical activity barriers than the group with more extended experience (more than 10 years).The current results are in agreement with evidence that suggested that the effect of long work hours on physical activity levels and meeting the recommendations among employees working status (including occupations type, and years of experience) consider as an effect modifier in the relationship, affecting differently across occupations (Cook & Gazmararian, 2018). Research studies have related the impact of working hours on employees physical activity levels to the professional level occupation, whereas, those with higher occupational level were more likely to be more active and meet the leisure-time physical activity recommendations (Kirk & Rhodes, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…The current study has indicated that the willing power barrier was the third most significant barrier of physical activity and exercise among participants. Despite women's awareness of the benefits and need of meeting the recommendation of daily physical activity, participants of previous research studies have reported that they know how to enhance their daily physical activity but wouldn't because they feel "Lazy" (Cook & Gazmararian, 2018). Women's willpower as perceived barrier could also be related to the fact that it has been reported as not a priority when planning leisure time schedules (Segar, Taber, Patrick, Thai, & Oh, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations